Analisis keputusan wanita bekerja dan kontribusinya pada ekonomi rumah tangga di Kota Jambi - Yulia Desti Sukma; Heriberta Heriberta; Etik Umiyati (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
The purpose of this study is to analyze the socio-economic conditions of women, what factors influence the decisions of working women and how much the income contribution of women working towards the household economy. In determining the location of the study, this study used a